Analysis of Adoption Practices of SRI in Tribal Region of Sundargarh District in Odisha - Ashish Kerketa, Ashish Kerketa; Plabita Ray, Plabita Ray; Chitrasena Padhy, Chitrasena Padhy; Santanu Kumar Patra, Santanu Kumar Patra; Rabindra Kumar Raj, Rabindra Kumar Raj; Nibedita Mishra, Nibedita Mishra; V. Prasanna, V. Prasanna (Indian Journal of Extension Education, 2025)
The study was conducted in 2020 and data was collected randomly from ten Gram panchayats spread across five blocks of Sundargarh district of Odisha, the total farmers being 96 in the tribal area who had stopped using System of Rice Intensification (SRI) in paddy cultivation. It was found that in spite of all efforts and incentives the farmers were not developing enthusiasm to continue the method. Therefore, the goal of the present study was to assess the causes of discontinuance in SRI method of rice cultivars. It revealed that poor adoption of raising nursery beds at 80-100 cm height, putting seedlings in a thin metal sheet for transplanting, applying recommended dose of manure or vermicompost and green manuring, applying nitrogen in three splits, alternate drying and wetting of the main field, light irrigation during hair line cracks and applying minimum of four weeding at 10 days interval. Path analysis revealed that the socio-economic attribute education through housing pattern, annual income, extension contact, social participation, agricultural implements use significantly influenced adoption practices.